Holmium laser enucleation of the prostate followed by high-intensity focused ultrasound treatment for patients with huge prostate adenoma and localized prostate cancer: 5-Year follow-up - Horiuchi, Akira (Prostate Int, 2016)
BACKGROUND: To evaluate the efficacy of holmium laser enucleation of the prostate (HoLEP) followed by high-intensity focused ultrasound (HIFU) for patients with huge prostate adenoma and localized prostate cancer (CaP) and compare the morbidity and efficacy results with those observed in a similar population treated only with HIFU for a follow-up period of up to 5 years. METHODS: The present retrospective study included 30 CaP patients who underwent HIFU alone and 10 patients who underwent HoLEP followed by HIFU. Selection criteria for this study were no previous treatment for CaP, aged 60 years or older, cT1c-T2N0M0, prostate volume of 30 mL or more, and a follow-up period of 5 years or more. Prostate-specific antigen (PSA) biochemical recurrence-free survival (RFS) rates and functional outcomes including complications and uroflowmetry after HIFU were compared between the HIFU monotherapy and HoLEP + HIFU groups. RESULTS: The enrolled patients had a mean age of 70.3 years and 68.8 years in the HIFU monotherapy and HoLEP + HIFU groups, respectively. The 5-year PSA biochemical RFS rates of the two groups were similar (HIFU monotherapy group: 57.2%; HoLEP + HIFU group: 67.5%). The duration of indwelling urethral catheter after HIFU significantly decreased in the HoLEP + HIFU group compared with the HIFU monotherapy group (15.5 ± 2.7 days vs. 27.5 ± 2.3 days, P = 0.022). In terms of functional outcomes, patients who received HoLEP + HIFU had significantly higher maximum (12 months: P = 0.015, 36 months: P = 0.014) and average (36 months: P = 0.002, 60 months: P = 0.047) flow rates than those who received HIFU monotherapy. The frequency of urethral stricture (13.3% vs. 0%), symptomatic urinary tract infection (10.0% vs. 0%), and bladder stone and urethrorectal fistula (3.3% vs. 0%) tended to be higher in the HIFU monotherapy group as compared with the HoLEP + HIFU group. CONCLUSION: The HoLEP + HIFU treatment decreases urinary catheterization time and improves post-treatment urinary status without additional morbidity.